1996
DOI: 10.1152/jn.1996.76.5.3249
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the human vestibuloocular reflex during saccades: probing by high-frequency oscillation and torque pulses of the head

Abstract: 1. We probed the gain and phase of the vestibuloocular reflex (VOR) during the execution of voluntary gaze saccades, with continuous oscillation or acceleration pulses, applied through a torque helmet. 2. Small-amplitude (< 1 degree), high-frequency (10-14 Hz) head oscillations in the horizontal or vertical plane were superimposed on ongoing horizontal gaze saccades (40-100 degrees). Torque pulses to the head ("with" or "against" gaze) were superimposed on 40 degrees horizontal saccades. Eye and head movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 29 publications
5
40
0
Order By: Relevance
“…2 A, gray traces). As observed previously, perturbed gaze shifts remained accurate following head perturbations ( p ϭ 0.46; paired t test, matched perturbed vs control trials) (Laurutis and Robinson, 1986;Guitton and Volle, 1987;Tomlinson, 1990;Tabak et al, 1996;Cullen et al, 2004) Importantly, the applied transient head perturbations did not completely interrupt the gaze shift (i.e., gaze velocity was not driven to zero velocity for a sustained time interval). Rather, they modified ongoing gaze shifts in two critical ways: (1) gaze shift durations increased significantly ( p Ͻ 0.05) (Fig.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…2 A, gray traces). As observed previously, perturbed gaze shifts remained accurate following head perturbations ( p ϭ 0.46; paired t test, matched perturbed vs control trials) (Laurutis and Robinson, 1986;Guitton and Volle, 1987;Tomlinson, 1990;Tabak et al, 1996;Cullen et al, 2004) Importantly, the applied transient head perturbations did not completely interrupt the gaze shift (i.e., gaze velocity was not driven to zero velocity for a sustained time interval). Rather, they modified ongoing gaze shifts in two critical ways: (1) gaze shift durations increased significantly ( p Ͻ 0.05) (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Numerous studies have shown that gaze accuracy is unaffected by the passive application of head perturbations during an ongoing gaze shift (Tomlinson and Bahra, 1986;Pelisson et al, 1988;Tabak et al, 1996). Dynamic gaze feedback models incorporate this experimental result using their single feedback loop.…”
Section: Feedback and The Control Of Gaze Shiftsmentioning
confidence: 99%
“…The gain was near unity for stimulation of the anterior zone but substantially suppressed, even negative, when stimulation was applied in the intermediate zone, which evoked large amplitude gaze shifts. Their results are more in line with the accepted notion that the VOR gain is dynamically attenuated during visually-guided gaze shifts (Laurutis and Robinson 1986;Pélisson and Prablanc 1986;Tomlinson and Bahra 1986;Guitton and Volle 1987;Pélisson et al 1988;Lefèvre et al 1992;Tabak et al 1996;Cullen 1998, 2002;. How can this discrepancy be resolved?…”
Section: Status Of the Vor Gain: Comparison With Previous Studiessupporting
confidence: 82%
“…1A and added dashed lines as our interpretation: the variations in peak velocity seem proportional to those in amplitude. We observed a similar pattern when plotting a main sequence from our earlier experiments (Tabak et al 1996).…”
Section: Introductionsupporting
confidence: 80%